Implementing a Multisite Clinical Trial in the Midst of an Ebola Outbreak: Lessons Learned From the Sierra Leone Trial to Introduce a Vaccine Against Ebola. (18th May 2018) - Carter, Rosalind J; Idriss, Ayesha; Widdowson, Marc-Alain; Samai, Mohamed; Schrag, Stephanie J; Legardy-Williams, Jennifer K; Estivariz, Concepcion F; Callis, Amy; Carr, Wendy; Webber, Winston; Fischer, Marc E; Hadler, Stephen; et al.
Abstract: The Sierra Leone Trial to Introduce a Vaccine against Ebola (STRIVE), a phase 2/3 trial of investigational rVSV∆G-ZEBOV-GP vaccine, was conducted during an unprecedented Ebola epidemic. More than 8600 eligible healthcare and frontline response workers were individually randomized to immediate (within 7 days) or deferred (within 18–24 weeks) vaccination and followed for 6 months after vaccination for serious adverse events and Ebola virus infection. Key challenges included limited infrastructure to support trial activities, unreliable electricity, and staff with limited clinical trial experience. Study staff made substantial infrastructure investments, including renovation of enrollment sites, laboratories, and government cold chain facilities, and imported equipment to store and transport vaccine at ≤−60 o C. STRIVE built capacity by providing didactic and practical research training to >350 staff, which was reinforced with daily review and feedback meetings. The operational challenges of safety follow-up were addressed by issuing mobile telephones to participants, making home visits, and establishing a nurse triage hotline. Before the Ebola outbreak, Sierra Leone had limited infrastructure and staff to conduct clinical trials. Without interfering with the outbreak response, STRIVE responded to an urgent need and helped build this capacity. Clinical Trials Registration. ClinicalTrials.gov [NCT02378753] and Pan African Clinical Trials Registry [PACTR201502001037220].